The mechanism of cytoskeleton protein β-actin and cofilin-1 of macrophages infected by Mycobacterium avium - Wang, Jianjun (e-Century Publishing Corporation, 2016)

(untitled) (Am J Transl Res)
Cytoskeleton proteins and their regulation proteins could be influenced seriously in Mycobacterium tuberculosis infection host cells leading to the apoptosis of host cells. Macrophages infected by Mycobacterium avium were detected from cell morphology and genome levels to analyze changes of the cytoskeleton of M. avium infection macrophages. Then the expression of β-actin, cofilin-1 proteins in M. avium infected macrophages were analyzed by western blotting, and the apoptosis of M. avium infection macrophages were tested by flow cytometry. Results indicated that the morphology and genomic DNA of M. avium infection macrophages were not damaged significantly. Meanwhile, β-actin gene and its proteins in M. avium infection macrophages were both decreased, but its regulatory protein cofilin-1 was expressed conversely. Furthermore, macrophages could be induced to apoptosis due to M. avium infection by cytoskeleton changes. These findings contributed us to understand that macrophages infected by M. avium could be lead to apoptosis by regulating cytoskeleton protein β-actin or its regulatory protein cofilin-1.